Functionality of Bread and Beverage Added with Brosimum alicastrum Sw. Seed Flour on the Nutritional and Health Status of the Elderly - Rodriguez-Tadeo, Alejandra (2021)
Physiological changes in elderly individuals (EI) can contribute to nutritional deteriora‐ tion and comorbidities that reduce their quality of life. Factors such as diet can modulate some of these effects. The aim was to evaluate the functionality of foods added with Brosimum alicastrum Sw. seed flour in EI. EI (n = 23) living in nursing home conditions agreed to participate. A control stage was carried out (30 days) and subsequently, an intervention stage (30 days) was realized in which a muffin and a beverage, designed for EI, were added to the participants’ their usual diet. In both stages, anthropometric parameters, body composition, nutritional status, dietary intake, sarcopenic status, cognitive and affective states, biometric parameters, and total phenolic compounds (TPC), and antioxidant capacity in foods and plasma of EI were determined. The results showed that the consumption of the foods improved the energy intake and preserved the muscle reserves of the EI. The EI gained body weight (+1.1 kg), increased their protein (+18.6 g/day; 1.5 g/kg BW/day), dietary fiber (+13.4 g/day), iron (+4.4 mg/day), zinc (+1.8 mg/day), folic acid (+83.4 μg/day) consumption while reducing their cholesterol (−66 mg/day) and sodium (−319.5 mg/day) consumption. LDL‐C lipoproteins reduced (14.8%) and urea (33.1%) and BUN (33.3%) increased. The TPC increased (7.8%) in the plasma, particularly in women (10.7%). The foods improve the EI nutritional status, and this has a cardiovascular protective effect that can benefit the health of the EI.